(untitled) (The Pretoria Student Law Review, 2023)
This article aims to determine the most appropriate liability regime for accidents caused by Autonomous Vehicles (AVs) resulting in personal injury or death. The motivation for this research lies in the fact that AVs are currently not adequately regulated within South African legislation. Seeing as the regulation of AVs should begin sooner rather than later, it is essential to examine the capability of the Road Accident Fund (RAF) to provide for AVs and consider other possible liability regimes. The article will focus on the RAF Act and the possibility of including the definition of AVs under section 1 thereof. The RAF Act currently defines a motor car as a motor vehicle designed or adapted for the conveyance of not more than ten persons, including the driver. The article will analyse the Civil Aviation Act (Aviation Act) to propose a regime where the owners of AVs are required to have private insurance. Section 8(5) of the Aviation Act will form the basis for the proposed regime change as this section holds that a registered owner or operator of an aircraft must have insurance as prescribed for any damage or loss that is caused by an aircraft to any person or property on land or water.